Frontispiece: Synthetic Approaches to Triarylboranes from 1885 to 2020. Issue 24 (28th April 2021) - Berger, Sarina M.; Ferger, Matthias; Marder, Todd B.
Abstract : The review article presented by T. B. Marder et al. on page 7043, summarizes the synthetic developments that have been made in the synthesis of triarylboranes throughout the years from their first appearance in 1885 to the present. It is shown that, over time, developments in other fields of research enriched triarylborane chemistry by developing new organometallic reagents or boron sources, which led to new synthetic strategies and opened the door for diverse applications. Investigation of reactivities and other molecular properties of triarylboranes led to the first commercially available products by the middle of the 20th century. With increasing interest in this field of research, new potential applications of such compounds continue to arise. This review article aims to provide guidance for researchers to find the best synthetic strategy for preparing new compounds containing the triarylborane motif.